2020
DOI: 10.1111/jfbc.13422
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin downregulates inflammation‐mediated nitric oxide overproduction and potentiates endogenous antioxidant status during hyperglycemia

Abstract: Nitric oxide is a key regulating factor for physiological functions, when elevated during inflammatory conditions, NO, can lower endogenous antioxidants level. Naringenin, a bioflavonoid has shown to possess anti-inflammatory action. However, its role in NO-mediated responses has not been elucidated till date. This study was designed to investigate antioxidant potential of naringenin against inflammation-mediated nitric oxide overproduction and antioxidant status with an improved glycemic profile in diabetic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The therapeutic potential of hesperidin has been confirmed recently (Rehman et al, 2020b). This flavanone improved leptin and insulin resistance, IL-6 and TNF-α more significantly compared to the reference drug Orlistat used in high fat diet (HFD)-induced obese rats.…”
Section: Antibacterial Effectmentioning
confidence: 86%
“…The therapeutic potential of hesperidin has been confirmed recently (Rehman et al, 2020b). This flavanone improved leptin and insulin resistance, IL-6 and TNF-α more significantly compared to the reference drug Orlistat used in high fat diet (HFD)-induced obese rats.…”
Section: Antibacterial Effectmentioning
confidence: 86%
“…Naringin is a kind of citrus flavonoid with a variety of biological activities including significant anti-inflammatory activities [ 151 ]. Studies showed that naringin could inhibit the release of pro-inflammatory cytokine IL-1β and induce the expression of anti-inflammatory factor interleukin-10 (IL-10) and transforming growth factor β1(TGF-β1) [ 152 ].…”
Section: Natural Products With Anti-inflammatory Effects In Alzheimer...mentioning
confidence: 99%
“…In fact, naringenin is able to ameliorate hyperglycemia and to improve the secretion of insulin. Moreover, it has an action on the inflammatory status by decreasing cytokines like TNFα and IL-6 and increasing the activity of SOD [ 105 ]. Naringenin and hesperetin are aglycones, but they are often found in their glycosylated form called naringin (naringenin + neohexperidose) and hesperidin (hesperetin + rutinose).…”
Section: Structure and Function Of Grape Polyphenolmentioning
confidence: 99%